Market timing and Debt-Equity Choice of Nepalese Firms - Silwal, Prem Prasad (The International Research Journal of Management Science, 2018)
This paper aims to analyze the multivariate discriminant analysis of debt-equity choice in Nepalese non-financial firms for the period of 1992 to 2013. It is based on pooled cross-sectional data of 18 firms (263 observations) whose stocks are listed in Nepal Stock Exchange. The study finds that firm issue equity when their stock prices are high. The result further reveals that firms are strongly influenced by market conditions and the past history of security prices in issuing between equity and debt. Discriminant analysis also shows that External financing weighted average market to book ratio, market to book ratio and leverage pattern are the major determinants of issuing equity or debt. Finally, the results are consistent with the notion that market timing variables have negative impact on leverage.